2015
DOI: 10.1159/000438456
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Mapping of Gyral and Sulcal Patterns of Cortical Thickness and Brain Volume Regain during Early Alcohol Abstinence

Abstract: We explored brain volume recovery in terms of cortical thickness (CTh; gyral, sulcal pattern) and surface area (SA), as well as subcortical volume recovery in the first 2 weeks of abstinence in 49 alcohol-dependent patients (ADPs). A widespread reduction of CTh in ADPs at day 1 of abstinence compared to healthy controls, with more pronounced differences in sulci relative to gyri was found. After 2 weeks of abstinence, partial recovery to varying degrees of CTh loss in ADPs was observed for several regions. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 59 publications
1
17
0
Order By: Relevance
“…Partial recovery of cortical thickness was also found after only 2 weeks of sobriety with full normalization seen in medial OFC and rostral ACC. Regeneration of sulci was more pronounced here in all affected brain areas than in gyri . Another study showed significant normalization of hippocampal GM volume within the first 2 weeks of abstinence in AD, especially in those with greater withdrawal severity at baseline .…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…Partial recovery of cortical thickness was also found after only 2 weeks of sobriety with full normalization seen in medial OFC and rostral ACC. Regeneration of sulci was more pronounced here in all affected brain areas than in gyri . Another study showed significant normalization of hippocampal GM volume within the first 2 weeks of abstinence in AD, especially in those with greater withdrawal severity at baseline .…”
Section: Resultsmentioning
confidence: 91%
“…Interestingly, some studies did not find significant WM differences between AD and controls , although WM volume gain has been detected with abstinence. DTI is probably more sensitive to WM change than structural MRI, as detailed architecture of white matter tissue can be analyzed by visualizing molecule diffusion patterns .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition to ventricular shrinkage, she exhibited resolution of radiological evidence for central pontine myelinolysis, which if left untreated, can be fatal (Lampl & Yazdi, 2002;). In addition to single case studies, an ever-increasing number of longitudinal MRI studies on groups of alcoholics report significant changes in regional brain volumes (e.g., Cardenas, Studholme, Gazdzinski, Durazzo, & Meyerhoff, 2007;Rohlfing, Sullivan, & Pfefferbaum, 2006;Shear, Jernigan, & Butters, 1994;Wang et al, 2016;Yeh, Gazdzinski, Durazzo, Sjostrand, & Meyerhoff, 2007). An early study imaged alcoholics approximately a week after detoxification and again approximately 3 weeks later, at the end of a 28-day VA inpatient treatment regime with enforced abstinence.…”
Section: Learn That Sustained Sobriety Can Results In Improvement In Bmentioning
confidence: 99%
“…Cortical thickness is genetically and phenotypically distinct from cortical surface area and volume (Kremen et al, 2010; Panizzon et al, 2009; Winkler et al, 2010), and it is related to neurocognition in healthy adults and adolescents (Choi et al, 2008; Dickerson et al, 2008; Fjell et al, 2006; Schilling et al, 2013; Walhovd et al, 2006) and those with a cocaine use disorder (Makris et al, 2008). Cortical thickness is reputed to be more sensitive to neurodegenerative processes than cortical volumes (Hutton et al, 2009); therefore, this morphometric may increase the ability to detect more subtle structural abnormalities than volumes or density measures and/or be differentially affected by addictive disorders compared to volumes and surface area (Durazzo et al, 2011b; Wang et al, 2016). Taken together, cortical thickness may serve as a proxy for the integrity of cortical cytoarchitecture (Makris et al, 2007).…”
Section: Introductionmentioning
confidence: 99%